Bivalent Ligands for the Serotonin 5-HT(3) Receptor - Cappelli, Andrea (American Chemical Society, 2011)
[Image: see text] The serotonin 5-HT(3) receptor is a ligand-gated ion channel, which by virtue of its pentameric architecture, can be considered to be an intriguing example of intrinsically multivalent biological receptors. This paper describes a general design approach to the study of multivalency in this multimeric ion channel. Bivalent ligands for 5-HT(3) receptor have been designed by linking an arylpiperazine moiety to probes showing different functional features. Both homobivalent and heterobivalent ligands have shown 5-HT(3) receptor affinity in the nanomolar range, providing evidence for the viability of our design approach. Moreover, the high affinity shown by homobivalent ligands suggests that bivalency is a promising approach in 5-HT(3) receptor modulation and provides the rational basis for applying the concepts of multivalency to the study of 5-HT(3) receptor function.